The Information Disclosure Strategy of Single versus Multiple Benchmarks in Earnings Announcements - Sri Wahyuni; Jogiyanto Hartono; Supriyadi Supriyadi; Ertambang Naharto (The Indonesian Journal of Accounting Research, 2018)
Abstract: This study is aimed to test the impact of single versus multiple benchmarks earnings information disclosure strategy towards financial users’ behavior in estimating future earnings. The study is important because it links behavioral aspects between the ways of providing and using earnings information based on multiple reference point theory of psychology. Using experimental factorial mix design 2x3x2 with 58 investor and non-investor participants, the result indicates that earnings disclosure strategy of single versus multiple benchmarks influences participant's judgments. Specifically, the multiple benchmarks are more effective than a single benchmark used to estimating future earnings. This finding is consistent with some priors studies of Schrand and Walther (2000), Krische (2005),  Han and Tan (2007) and Wahyuni and Hartono (2010, 2012, 2014). Abstract: This study is aimed to test the impact of single versus multiple benchmarks earnings information disclosure strategy towards financial users’ behavior in estimating future earnings. The study is important because it links behavioral aspects between the ways of providing and using earnings information based on multiple reference point theory of psychology. Using experimental factorial mix design 2x3x2 with 58 investor and non-investor participants, the result indicates that earnings disclosure strategy of single versus multiple benchmarks influences participant's judgments. Specifically, the multiple benchmarks are more effective than a single benchmark used to estimating future earnings. This finding is consistent with some priors studies of Schrand and Walther (2000), Krische (2005),  Han and Tan (2007) and Wahyuni and Hartono (2010, 2012, 2014).